Venturia oleaginea, the Causal Agent of Peacock Eye Disease in Olive, Maintains Monocyclic and Polyetic Characteristics in a Mediterranean Climate - Ygzao, David (Plant disease, 2025)
Olive leaf spot, also called peacock eye disease, is caused by the hemibiotrophic plant pathogen Venturia oleaginea. Disease symptoms develop on the upper side of leaves; infected leaves eventually abscise; and in severe epidemics, the trees are completely defoliated. Despite the vast knowledge gained about the pathogen and the disease since it was first described in 1845, observations made in recent years in commercial olive groves in Israel remain unexplained. The long-term objective of this study was to establish guidelines for disease management strategies in commercial olive groves in Israel. To achieve this, we first needed to comprehend the development and progression of the disease in the region. We determined that in each growing season, infections could occur in both autumn and spring. Furthermore, there were two episodes of disease development: the first between the end of autumn and the beginning of winter, and the second between the spring and early summer. The data were utilized to propose a model for peacock eye development which implies that V. oleaginea maintains monocyclic and polyetic characteristics in the Mediterranean climatic conditions prevailing in Israel: the disease is monocyclic because it completes only one disease cycle within a certain growing season; polyetic because infections occurring in one growing season remain asymptomatic until the succeeding season